Hepatitis B virus lymphotropism: emerging details and challenges. Issue 1 (2nd January 2018) - Joshi, Shivali S.; Coffin, Carla S.
Abstract: The hepatitis B virus (HBV) is predominantly a hepatotropic virus but also infects cells of the lymphatic system. HBV genomes (DNA, messenger (m)RNA, covalently closed circular (ccc) DNA) and proteins have been found in extrahepatic sites such as peripheral blood mononuclear cells (PBMC), lymph nodes, spleen, bone marrow and cerebrospinal fluid. HBV entry into hepatocytes occurs by binding of the HBV preS1 surface protein to its specific receptor, the bile acid transporter, sodium taurocholate co-transporting polypeptide (NTCP). Although the mechanism of HBV entry into lymphatic cells is unknown, the pre S1 encoded surface protein is thought to be involved. Extrahepatic HBV infection has been studied in both chronic HBV (CHB) and in occult HBV infection (OBI). Studies have shown that HBV genomes are present in different PBMC subsets from chronically infected carriers. Unique HBV variants have been found in PBMC compared to plasma or liver in both nucleos(t)ide analogue (NA) treated and untreated CHB carriers, suggesting replication and compartment specific evolution of HBV. In HBV coinfection, HBV genomes were found in PBMC from hepatitis C virus (HCV), human immunodeficiency virus (HIV) and hepatitis delta virus (HDV) co-infected individuals. Moreover, during pregnancy, the trans placental passage of HBV infected PBMC from highly viremic mothers to infants is one of the postulated means of vertical transmission of HBV. Taken together, HBV infection in extrahepatic sites (i.e., PBMC) is implicated in multiple facets of HBV pathogenesis such as persistence, viral evolution and vertical transmission.